A bio-inspired, plant-derived admixture for metakaolin blended cement mortars. (7th November 2022) - Qian, Xin; Li, Mengxiao; Wang, Jialai; Wang, Liang; Chen, Peiyuan; Fang, Yi; Wang, Xiaodong; Yang, Fan
Highlights: Tannic acid (TA) is exploited as an eco-friendly admixture to disperse MK. TA dispersion densifies the hydration products. Low-density calcium hydrate silicate was converted to high density by the TA dispersion. Compressive strength of cement mortar at 28d was enhanced up to 97% by TA dispersed MK. Abstract: Partially replacing ordinary Portland cement (OPC) with metakaolin (MK) can refine the pore structure, improve mechanical properties, and enhance the durability of concretes. However, MK tends to agglomerate due to its high surface area and high concentration of hydroxyl groups. To overcome this problem, this study exploits a plant-derived polyphenol, tannic acid (TA), as an eco-friendly admixture to disperse MK. Due to its similar chemical functional groups as the adhesive protein in the mussel byssus, TA can adhere to various surfaces like the mussel's adhesive protein. An experimental program was carried out to characterize the TA treated MK and investigate the effects of the proposed method on the properties of the cement paste and mortar. After mixing with the MK, TA can be adsorbed on the surface of MK particles, achieving deflocculation and dispersion of mineral grains by electrostatic repulsion forces and steric effect, significantly improving the workability of the mortar. Pore structure analysis suggests that TA dispersion densifies the hydration products, as revealed by the much-reduced gel and interhydrate pores. The nanoindentation results indicated that all low-density calcium hydrate silicate (CSH) was converted to high density by the TA dispersion, leading to a drastic improvement in the compressive strength of the produced mortars. As a result, the 28 days compressive strength of cement mortar prepared with TA dispersed MK was enhanced by up to 97 % compared with the one prepared without MK substitution, which exhibits great potential in reducing the carbon footprint of cement-based construction materials.